(3MGTjI JLQjO GdcdGes - (3GdMfaj GdYdhj GdOgdhj, ejQRGLGf (B- (3TeS GdOjf, MHjH Gddg Hf YHO Gddg, J (B994 (3g`s ((3fhGMj CQOHjds)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bhdg afGH Pdc (B.. (3MGUd hLg GdefGSHI Cfg deG cGf hLhO eJhba Ydi hLhO GdLhgQ acGf GdLhgQ ebOeG HGdWHY Ydi GdYQV abOeg HGdhVY Cj HGdPcQ (B...s
(3BNQgG (B:s
... (3jef Cf jbGd Cf gPG Gdchf gh Gdchf GdChd aj GdNjQ GdChd aJTGHg GdMQcGJ ef MjK CfgG aj GdMjR GdChd achfg eeGKdG ddSchf djS ChdG ef chfg eeGKdG ddMQcI Hd dG jHYO (B...(3Gdchf Ohf GdNjQ JCed(B. (3bO JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\527s
(3cTa GdXfhf (B1\346s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds